Investments in the Industry Field in the Emerging Markets - Milosev, Ivana; Tesic, Zdravko (International Journal of Industrial Engineering and Management, 2011)
The main idea of this paper is researching Global Investment possibilities and creating strategies for Investments in the Industry Field. As a proposal for the recovery from the recession there should be made strategies for the Emerging countries, which are very attractive for investments. Since the optimal capital allocation means investment with the highest income and the minimal risk, there should be chosen markets which are often not in the country of the investors but give positive investment results. Because of that, one of the most recommendable investment solutions in the Industry field on the Global market is foreign direct investment in the Emerging Countries. Beside the fact the investors have good subventions and other market conditions, at the same time that is important for Global Economy and Financial market as well. Investments on the Global Market include a large number of possibilities for choosing the optimal investment solution, since there are also investment possibilities on the Emerging Markets and new industrial fields. The main Problem of the Researching which will be presented in this paper is a need for Investments in Industry field in the period of Global Economic Crisis. Besides analysing Foreign direct investments in Emerging Markets, in this Paper there will be given some Investment proposals for Investing in Serbia, as an Emerging country which follows Global investment trends. Article history: Received (17.05.2011); Revised (21.09.2011); Accepted (24.10.2011)